Ovoo phenomenon of the Mongolians: Influencing well-being through the human–nature and human–spiritual relationships - Batmunkh, Buyandelger; Tuya, Amgalan; Sandagjav, Solongo; Unenbat, Munkhdagva; Shagdar, Ichinkhorloo (The New Research of Tuva, 2025)
The Mongolian ovoo is a cairn of stones and wood branches found in a natural environment. Because of stereotypes, ovoo is only understood as a place of worship or symbol, but it is a unique way to influence well-being through the human–nature and human–spiritual relationships. Hence, the aim of our study was to review the literature and provide an overview investigating the effects of the ovoo on the well-being of the Mongolians. The ovoo phenomenon has culture-specific characteristics and philosophical aspects related to identity, tradition and conservation, but the most interesting issue is undoubtedly its influence on well-being. In 2017, the ovoo and Mongolian worshipping rituals were inscribed on UNESCO’s List of Intangible Cultural Heritage in Need of Urgent Safeguarding as part of “Mongolian traditional practices of worshipping the sacred sites”. Understanding how the ovoo influences well-being through the human–nature and human–spiritual relationships is essential for addressing current challenges. The ovoo is of a wide significance, there are many ovoos in all areas where the Mongolians live. It should be emphasized again that the ovoo ritual is not only an intangible cultural heritage, but also a phenomenon that has a positive effect on well-being by interacting between human and nature in the spiritual sphere.